How Talking Cures: Revealing Freud's Contributions to All Psychotherapies - Jaffe, Lee (Rowman & Littlefield Publishers, 2014)
Sigmund Freud repeatedly revised his understanding of how our minds work, how to understand mental illness, and how to relieve emotional, psychological suffering. With each revision, however, he did not methodically integrate previous ideas with newer ones. In How Talking Cures: Revealing Freud's Contributions to All Psychotherapies, a careful review of his concepts at each stage of his thinking reveals six different ways that talking cures—six distinct generic modes of therapeutic action by which all present-day psychotherapies work. Lee Jaffe demonstrates how these therapeutic actions can link treatment recommendations to individual diagnoses, and how they function during treatment itself. Different views of how psychoanalytic treatments work are analyzed according to their emphasis or de-emphasis of these six modes of therapeutic action. As a result, comparisons of all approaches to talking cures, and decisions about the choice of treatment for a given patient can be grounded in an understanding of the essential ways that each therapeutic procedure works, rather than an allegiance to what providers happened to be taught during their training.